THE EFFECT OF PROFITABILITY, FIRM SIZE, AND LEVERAGE ON TRIPLE BOTTOM LINE DISCLOSURE IN COMPANIES LISTED IN THE SRI-KEHATI INDEX 2019-2021 (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
This study aims to determine: (1) the partial effect of profitability on Triple Bottom Line disclosure, (2) the partial effect of firm size on Triple Bottom Line disclosure, (3) the partial effect of leverage on Triple Bottom Line disclosure in companies listed on the Sri-Kehati index in 2019-2021. This research uses secondary data obtained from financial reports and the company's Sustainability Report. The population in the study was 37 companies and used purposive sampling in selecting the sample, resulting in 12 companies. The secondary data obtained was processed using multiple linear regression analysis techniques and using the SPSS 20 analysis tool. The results of this study show that: (1) profitability affects the percentage of Triple Bottom Line disclosure, (2) firm size affects the percentage of Triple Bottom Line disclosure, (3) leverage has no affect on the percentage of Triple Bottom Line disclosure.
Keywords: Profitability; firm size; Leverage; Triple Bottom Line